UJI SIFAT FISIS BATAKO PEJAL BERBAHAN CAMPURAN SERAT ISI TANGKAI DAUN SAGU - R. Suppa; L. Sulaiman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
The Solid concrete bricks made from a mixture of with sago leaf stalks fiber were 390 mm long, 90 mm wide, and 100 mm thick with three combinations of cement: aggregate ratios, namely 1: 5,1: 6, and 1: 7. These were further divided into 4 compositions of the aggregate mixture (sand: fiber), 100%: 0%, 75%: 25%, 50%: 50%, and 25%: 75%. The observation stage showed that the brick made from an external viewpoint was very feasible, like, the surface is not defective / hollow and was not easily damaged if touched. The treatment of the brick was carried out for 28 days after being made, then tested and the average mass was obtained at least in the combination ratio of cement: aggregate 1: 5 with an agerat composition of 25% sand: 75% fiber, namely 4.46 Kg. For the compressive strength test results, all the test samples made meet SNI 03-0349-1989 in the quality range I and quality II. The compressive strength value was in the combination of the ratio of cement: aggregate 1: 7 with a composition of 25% sand: 75% fiber, namely 70 Kg / Cm2 which is classified as quality II, while the largest is in the combination of cement: aggregate ratio 1: 5 with a composition of 100% sand which is 167 Kg / Cm2. From the test results, it can prove that the concrete blocks made from a mixture of sago leaf stalks fiber in terms of compressive strength pass the SNI quality test..